Implementation Of Digital Media Agumented Reality Based On Integrated Neuroscience Of The Qur'an To Improve Students' Physical Insight And Spiritual Attitudes In The Era Of Society 5.0 - Lailatul Nuraini; Jalis Syarifah; Halimatus Sa’diyah; Moh Kelvin; M. Athar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Technological developments in the 21st century have had a significant impact on various fields, including education. This study examines the effectiveness of the use of Augmented Reality (AR)-based learning media integrated with neuroscience and Qur'anic values in improving students' understanding of physics and spiritual attitudes in the Society 5.0 era. The research was conducted in two Islamic-based schools, namely SMA Darussalam Blokagung and MA Al-Amiriyyah Blokagung, using quantitative methods with pre-test and post-test. The results showed that AR learning media significantly improved students' understanding of physics concepts and spiritual attitudes, as evidenced by the difference in pre-test and post-test scores as well as the results of the N-Gain test which showed the effective category, with an average N-Gain score of 77.12% at SMA Darussalam Blokagung and 76.05% at MA Al-Amiriyyah Blokagung. In addition, students' spiritual attitudes also increased with the average questionnaire score showing the category of "Very Good". This study concludes that the integration of AR technology in learning is effective in improving academic understanding and the development of students' spiritual character.